2016
DOI: 10.1515/revneuro-2015-0029
|View full text |Cite
|
Sign up to set email alerts
|

The difference between electrical microstimulation and direct electrical stimulation – towards new opportunities for innovative functional brain mapping?

Abstract: AbstractBoth electrical microstimulation (EMS) and direct electrical stimulation (DES) of the brain are used to perform functional brain mapping. EMS is applied to animal fundamental neuroscience experiments, whereas DES is performed in the operating theatre on neurosurgery patients. The objective of the present review was to shed new light on electrical stimulation techniques in brain mapping by comparing EMS and DES. There is much controversy as to whether the use of DES duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 112 publications
0
25
0
Order By: Relevance
“…However previous studies were performed at a very low frequency (1 Hz) and although single-pulse stimuli can produce CCEPs and ACEPs, it has not been yet demonstrated that DES at higher frequency affects the whole network in the same manner [2,3]. In contrast, 100 ms seems to be a sufficient time-window that facilitates real-time averaging to detect these CCEPs and ACEPs for further on-line analysis of brain connectivity during the surgery.…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…However previous studies were performed at a very low frequency (1 Hz) and although single-pulse stimuli can produce CCEPs and ACEPs, it has not been yet demonstrated that DES at higher frequency affects the whole network in the same manner [2,3]. In contrast, 100 ms seems to be a sufficient time-window that facilitates real-time averaging to detect these CCEPs and ACEPs for further on-line analysis of brain connectivity during the surgery.…”
mentioning
confidence: 92%
“…Its use lowers the probability of resecting essential functional areas near or within the tumor. However, the electrophysiological effects of DES remain poorly understood, locally and at a more remote distance [2,3]. The investigation of this topic requires in part the recording of evoked potential.…”
mentioning
confidence: 99%
“…As such, 5 functional mapping aids in the identification of non-operational tissues important to 6 excise, and the prevention of neuropsychological complications induced by the excision 7 1/13 of operational tissue and tracts (fasciculi of axons). Despite the demonstrated utility of 8 intra-operative functional mapping, there is no standard approach to choose the 9 electrode parameters that are mostly set empirically [31]. Parameters of electrical 10 stimulation include pulse shape, pulse duration (P W ), stimulus amplitude (I), (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…1 B). Although bipolar biphasic stimulation is often used during 16 subcortical or cortical electrical stimulation [31], some clinical studies have also explored 17 cortical and subcortical responses using bipolar monophasic [13,30], monopolar 18 monophasic [10], and monopolar biphasic stimulation [10]. The effects of stimulation 19 parameters are difficult to assess experimentally, because closed-loop electrodes are not 20 routinely used for functional mapping and other fine assessments of the spatial-temporal 21 effects of stimulation parameters would require implantation of further electrodes used 22 only for research, and thus difficult to pass ethical review.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation